Isolated Large Glenoid Fracture and Acute Glenohumeral Dislocation in Elderly Patients: A Case Series Treated Surgically With Reverse Shoulder Arthroplasty and Augmented Glenoid - Giorgio Ippolito , MD; Michele Zitiello , MD; Giancarlo De Marinis , MD; Pierluca Di Lucia , MD; Michele F Surace , MD; Edoardo Franceschetti , MD; Pietro Gregori , MD; Rocco Papalia , MD; Luca Faoro , MD; Sergio Ferraro , MD (Journal of Shoulder and Elbow Arthroplasty, 2023)
Background One of the most frequent complications in patients affected by traumatic anterior dislocations is bony Bankart lesion. This study evaluates the clinical and functional outcomes of 10 patients with isolated large glenoid fracture and acute glenohumeral dislocation treated with reverse shoulder arthroplasty. Methods Patients older than 69 years who underwent reverse shoulder arthroplasty after isolated large glenoid fracture and acute glenohumeral dislocation between 2016 and 2022 at the same institute were selected. Shoulder range of motion and pain level was assessed. The impact on quality of life has been evaluated through four measures: the constant scale, the simple shoulder test (SST), the OXFORD scale, and The University of California—Los Angeles (UCLA) shoulder scale. Results The mean Constant score was 77.1 (range 68–84), the mean SST score was 9.4 (range 8–10), the Oxford score was 44.3 (range 35–48), and the UCLA shoulder scale was 27.1 (range 24–30). No reoperation was performed on any patient in this series. Conclusion Reverse shoulder arthroplasty for elderly patients with bony Bankart lesion and acute glenohumeral dislocation represents a valuable option in terms of clinical results, patient satisfaction and early- to medium-term complications.